PENGARUH BRAND IMAGE TERHADAP LOYALITAS KONSUMEN ROKOK MEREK TRUBUS ALAMI DI KOTA MALANG - Permana, Alkhaf; Rohman, Fatchur (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This study aims to determine the effect of variable Brand Image (Corporate Image, User Image and Product Image) on Consumer Loyalty to the brand of cigarettes Trubus Alami. This study using explanatory method that aims to determine the causal relationship between dependent and independent variables through partial and simultaneous hypothesis testing. The sampling technique used is probability sampling based on the opinions expressed 85 respondents in the sample obtained from a population of Malang. Regression analysis showed that the variable Brand Image (Corporate Image, User Image and Product Image) has a significant influence on customer loyalty. Testing hypotheses simultaneously, partial and dominant indicates that the independent variables affect the dependent variable. The correlation coefficient indicates that the correlation between dependent and independent variables are positive and strong. Keywords: Brand Image, Consumer Loyalty